Democratic Reforms in the Political Space of Kazakhstan: Recent Developments and Challenges (Халықаралық қатынастар және халықаралық құқық сериясы, 2022)
Kazakhstan faced the biggest political crisis in early January 2022 in over three decades since itsindependence in 1991. The crisis began with protests over rising fuel prices which turned into widespreadunrest followed by the crackdown and finally returning back to normalcy. It is believed that for the KazakhPresident, Kassym-Jomart Tokayev, this has been the biggest crisis during his presidency, but since hehas been able to control the situation it also offers an opportunity, particularly in matters of democraticreforms in the country. The article focusses on the recent developments and challenges concerning thedemocratic reforms undertaken in Kazakhstan. The main aim and objective is to review the key initiativestowards democratic reforms, especially the political reforms taken by Kazakhstan both before and duringthe period of Tokayev’s presidency. This is so because both the founding President as well as the currentPresident have believed that democratic reforms in the political space of Kazakhstan is indispensableif this Central Asian country has to make a move into the World’s top 30 most developed nations. Themethods used in this research mainly include qualitative that helped understand diverse opinions andexperiences of Kazakhstan in its democratic reforms programmes and initiatives. The article concludesthat despite a series of measures aimed at implementing the democratic reforms, it is still too early topredict how the democratic reforms in the political space of Kazakhstan will take shape in the future.Key words: Political Reforms, Kazakhstan-2030” Strategy, Kazakhstan-2050, Five InstitutionalReforms and 100 Concrete Steps.